3D printing of polymer-bonded magnets from highly concentrated, plate-like particle suspensions. (5th December 2019) - Shen, Alan; Peng, Xiaoguang; Bailey, Callum P.; Dardona, Sameh; Ma, Anson W.K.
Abstract: This paper reports the 3D printing of polymer-bonded magnets using highly concentrated suspensions of non-spherical magnetic particles. In a previous study, magnets of arbitrary shapes have been successfully fabricated using the UV-Assisted Direct Write (UADW) method. The magnetic remanence ( B r ) of the UADW magnets was limited by the type of magnetic particles used and the highest printable particle loading. Magnetic particles produced from melt spinning have better intrinsic magnetic properties, but their plate-like shape has resulted in a higher working viscosity, posing a major challenge in 3D printing with UADW. Inspired by the "Farris effect" in rheology, we mixed the plate-like particles of two different sizes to increase the polydispersity and reduce the overall viscosity of the mixture as the smaller particles can now fill the interstitial space between the larger ones. Using this rheological technique, a particle loading of as high as 65% by volume, or 93% by weight, was 3D printed. The resulting magnet has a density of 5.2 g/cm 3, an intrinsic coercivity ( H ci ) of 9.39 kOe, a remanence ( B r ) of 5.88 kG, and an energy product ( (BH) max ) of 7.26 MGOe, marking the highest values reported for 3D printed polymer-bonded magnets. Graphical abstract: Unlabelled Image Highlights: 3D printing of polymer-bonded magnets using plate-like, melt-spun magnetic particles yields stronger magnets. Mixing two different sizes of particles lowers the overall viscosity, taking advantage of the rheological Farris effect. Controlling the rheology enables 3D printing of polymer-bonded magnets with the best magnetic performance reported thus far.